Analysis of Optimal Portfolio Formation During the Covid-19 Pademic Using the Capital Asset Pricing Model (CAPM) Model for IDX-30 Shares in the 2020 Period: Analisis Pembentukan Portofolio Optimal di Masa Pandemi Covid-19 dengan Menggunakan Model Capital Asset Pricing Model (CAPM) pada Saham IDX-30 pada Periode 2020 - Kurniawan, Rifan Faris; Sari, Herlinda Maya Kumala (Indonesian Journal of Innovation Studies, 2023)
The study used the quantitative descriptive research design. The research population comprised all the stocks listed in the IDX30 index published biannually with a total of 30 stocks. The variables in the study were stock return, market return, stock risk, and market risk. The calculation of the expected return used the capital asset pricing model.The results of the study to find out the optimal portfolio of stocks by using capital asset pricing model were as follows. (1) The stock that made up the optimal portfolio were those of (1 adalah TBIG ( Tower Bersama Infrastructure Tbk.), MDKA (Merdeka Copper Gold Tbk.) dan UNTR ( United Tractor Tbk ) 2) The composition of the proportion of funds formed by using the Composite Stock Price Index as the market return proxy was allocated for the stocks of, 23% allocated for the stocks of TBIG ( Tower Bersama Infrastructure Tbk.) , 45%, allocated for the stocks of) MDKA (Merdeka Copper Gold Tbk.), 32%. allocated for the stocks of UNTR ( United Tractor Tbk ).